Building with paper : architecture and construction. - Knaack, Ulrich, ....-; Bach, Rebecca, ....-; Schabel, Samuel, ....- (Basel : Birkhäuser, 2023)
Paper and cardboard as sustainable building materials are currently the subject of research and testing in building practice. They can be produced inexpensively, are made from renewable raw materials and are completely recyclable. The focus of their application is on temporary uses, such as for transitional schools, emergency shelters or “microhomes”. Properly protected from moisture and fire, the material proves to be durable. Design and aesthetic qualities are by no means neglected, as case studies by Pritzker Prize winner Shigeru Ban demonstrate: the Chengdu Elementary School, the Paper Concert Hall in Aquila or the Cardboard Cathedral in Christchurch all provided a sign of hope after devastating earthquakes. This introduction explains the technology of building with cardboard and paper and shows a wide range of examples.
Bauen mit Papier
Keywords: Architectuur; Duurzaam ; bouwen